An analytical enrichment‐based review of structural genetic studies on keratoconus. Issue 4 (27th September 2018) - Panahi, Yunes; Azimi, Ali; Naderi, Mostafa; Jadidi, Khosrow; Sahebkar, Amirhossein
Abstract: Keratoconus is a progressive bilateral corneal protrusion that leads to irregular astigmatism and impairment of vision. Keratoconus is an etiologically heterogeneous corneal dystrophy and both environmental and genetic factors play a role in its etiopathogenesis. In this analytical review, we have studied all the genes that are structurally associated with keratoconus and have tried to explain the function of each gene and its association with other eye disorders in a concise way. In addition, using gene set enrichment analysis, it was attempted to find the most important impaired metabolic pathways in keratoconus. Several genetic studies have been carried out on keratoconus and several genes have been identified as risk factors involved in the etiology of the disease. In the current study, 16 studies, including nine association studies, five genome‐wide association studies, one linkage study, and one meta‐analysis, were reviewed and based on the 19 genes found, enrichment was performed and the most important metabolic pathways involved in the disease were identified. The enrichment results indicated that the two pathways, interleukin 1 processing and assembly of collagen fibrils, are significantly associated with the disease. Obviously, the results of this study, in addition to providing information about the genes involved in the disease, can provide an integrated insight into the gene‐based etiology of keratoconus and therapeutic opportunities thereof.